Acoustic smart sensors - Fernandes, Hugo Manuel Espinho Lebre (2018)
Nowadays buildings are being progressively integrated with an increasing number of sensors . Most of the times this sensors have quite speci c functions, butane sensors, propane sensors, carbon monoxide sensors, pyroelectric motion sensors, and this is what limits their eld of action. Introducing a certain level of autonomy to a sensor, i.e., send, process and receiving information can increase the interactivity and market attractiveness of a building. Within this point of view, and over-viewing the building conjuncture, it can be concluded that smart sensors will be installed during the construction, in recently constructed buildings, but also in buildings with several years which commonly have an physical electric network. This implies that this type of units will need to have an option to be retro tted and, to a certain degree, a simple installation. In this thesis, it is proposed the creation of an integrated solution using the wall of a room as a human interface. This system can establish communication with the gateway of a smart home using a previous researched, e cient and safe wireless protocol. Once the connection is established the gateway can execute a large variety of functions that can be programmed in the home central unit (gateway). The thesis hereby presented consists in a study of wireless communication protocols with respect to reliability, safety and practicality and in the research of the fusion between sensors, processing ability and communication interfaces with the intent of producing a prototype.